Benny and Penny in The big no-no! : a Toon Book - Hayes, Geoffrey (New York : Toon Books, 2009)
Two mice meet their new neighbor and discover that she is not as scary as they feared.
Booklist
Publisher's Weekly
Wilson's Children
Booklist, March 2009
Horn Book, October 2009
Kirkus Starred, May 2009
Keywords: Brothers and sisters -- Comic books, strips, etc -- Juvenile fiction; Mice -- Comic books, strips, etc -- Juvenile fiction; Neighbors -- Comic books, strips, etc -- Juvenile fiction; Brothers and sisters -- Fiction; Cartoons and comics; Mice -- Fiction; Neighbors -- Fiction; Comic books, strips, etc; Graphic novels; Mice -- Comic books, strips, etc -- Fiction; Neighbors -- Comic books, strips, etc -- Fiction; Siblings -- Comic books, strips, etc -- Fiction; Graphic novels